2023
DOI: 10.1103/physrevapplied.20.024030
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Quantum Illumination with Correlation-To-Displacement Conversion

Abstract: Entanglement is vulnerable to degradation in a noisy sensing scenario, but surprisingly, the quantum illumination protocol has demonstrated that its advantage can survive. However, designing a measurement system that realizes this advantage is challenging since the information is hidden in the weak correlation embedded in the noise at the receiver side. Recent progress in a correlation-to-displacement conversion module provides a route towards an optimal protocol for practical microwave quantum illumination. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…The correlation-to-displacement architecture was applied to microwave QI in [64] where it was extended to accommodate experimental inefficiencies associated with this regime. By introducing a loss to to the return mode, associated with nonideal coupling with the receiver, results showed that even with amplification a good quantum advantage compared to the ideal classical system can be guaranteed.…”
Section: Correlation-to-displacement Receivermentioning
confidence: 99%
“…The correlation-to-displacement architecture was applied to microwave QI in [64] where it was extended to accommodate experimental inefficiencies associated with this regime. By introducing a loss to to the return mode, associated with nonideal coupling with the receiver, results showed that even with amplification a good quantum advantage compared to the ideal classical system can be guaranteed.…”
Section: Correlation-to-displacement Receivermentioning
confidence: 99%
“…The full 6 dB advantage can be hypothetically attained with the complicated sum frequency generation (SFG) receiver and its extremely intricate upgrade, feed-forward SFG (FF-SFG) [13]. However, recent progress has been made towards saturating the full quantum advantage by proposing less demanding receiver architectures that only utilize heterodyne measurements and photodetection [14], [15]. Moreover, very recently the authors here [16] managed to achieve a 3dB advantage with only homodyne and heterodyne detection without the need for a joint signal-idler measurement.…”
Section: Introductionmentioning
confidence: 99%